Nicotinamide Increases Intracellular NAD+ Content to Enhance Autophagy-Mediated Group A Streptococcal Clearance in Endothelial Cells - Hsieh, Cheng-Lu; Hsieh, Shu-Ying; Huang, Hsuan-Min; Lu, Shiou-Ling; Omori, Hiroko; Zheng, Po-Xing; Ho, Yen-Ning; Cheng, Yi-Lin; Lin, Yee-Shin; Chiang-Ni, Chuan; Tsai, Pei-Jane; Wang, Shu-Ying; et al. (Frontiers in Microbiology, 2020)
Group A streptococcus (GAS) is a versatile pathogen that causes a wide spectrum of diseases in humans. Invading host cells is a known strategy for GAS to avoid antibiotic killing and immune recognition. However, the underlying mechanisms of GAS resistance to intracellular killing need to be explored. Endothelial HMEC-1 cells were infected with GAS, methicillin-resistant Staphylococcus aureus (MRSA) and Salmonella Typhimurium under nicotinamide (NAM)-supplemented conditions. The intracellular NAD+ level and cell viability were respectively measured by NAD+ quantification kit and protease-based cytotoxicity assay. Moreover, the intracellular bacteria were analyzed by colony-forming assay, transmission electron microscopy, and confocal microscopy. We found that supplementation with exogenous nicotinamide during infection significantly inhibited the growth of intracellular GAS in endothelial cells. Moreover, the NAD+ content and NAD+/NADH ratio of GAS-infected endothelial cells were dramatically increased, whereas the cell cytotoxicity was decreased by exogenous nicotinamide treatment. After knockdown of the autophagy-related ATG9A, the intracellular bacterial load was increased in nicotinamide-treated endothelial cells. The results of Western blot and transmission electron microscopy also revealed that cells treated with nicotinamide can increase autophagy-associated LC3 conversion and double-membrane formation during GAS infection. Confocal microscopy images further showed that more GAS-containing vacuoles were colocalized with lysosome under nicotinamide-supplemented conditions than without nicotinamide treatment. In contrast to GAS, supplementation with exogenous nicotinamide did not effectively inhibit the growth of MRSA or S. Typhimurium in endothelial cells. These results indicate that intracellular NAD+ homeostasis is crucial for controlling intracellular GAS infection in endothelial cells. In addition, nicotinamide may be a potential new therapeutic agent to overcome persistent infections of GAS.